Interaction between fibronectin fragments and immunoglobulin G in gingival crevicular fluid of patients with periodontal disease - Brajović Gavrilo; Nikolić-Jakoba Nataša; Popović Branka; Ilić Vesna; Mojsilović Sonja; Marković Dragana; Milošević-Jovčić Nadežda (Serbian Medical Society - Dental Section, Belgrade, 2015)
Introduction Fibronectin (FN) can interact with immunoglobulin G (IgG) molecules affecting the process of physiological elimination and causing abnormal deposition of immune complexes. The aim of the study was to analyze interaction between FN fragments and IgG molecules with different glycosylation profiles in gingival crevicular fluid (GCF) of patients with periodontal disease and healthy controls. Material and Methods The study included 30 patients with moderate and advanced periodontitis and 22 healthy subjects. IgG and FN content in GCF were measured as well as the presence of FN and galactose expression on IgG molecules. Results IgG content in GCF was five times higher in patients with moderate (p<0.01) and eight time higher in patients with advanced periodontitis (p<0.001) compared to healthy subjects. Also, hypogalactosylated forms of IgG were found in higher concentration in GCF of patients with advanced periodontitis compared to moderate periodontitis and healthy subjects (p<0.05). FN fragments of molecular mass 48 - 53 kDa were the most commonly found fragments in all three groups. Furthermore, in patients with advanced periodontitis, fibronectin fragments were attached to IgG molecules. Conclusion IgG and FN fragments form complexes in GCF in patients with periodontal disease and healthy subjects.